Freedom of Information and Records Management in Ghana - Adams, M. (African Journal of Library, Archives & Information Science, 2006)
In recent years there has been a drive towards the passage and implementation of freedom of information (FOI) legislations in many countries. Access to information is gaining acceptance as a necessary tool in ensuring the participation of the citizenry in democratic governance. An effective implementation of a freedom of information law is expected to lead to an open, transparent and accountable society. This paper identifies some countries which have passed and implemented the FOI laws and the relevance of the law in the Ghanaian context. Some basic elements of FOI are provided, a summary of the Ghanaian draft bill given and the basic information infrastructure in the country examined. The paper argues that an effective records management system is required to ensure a successful implementation of a freedom of information law and cites from the United Kingdom and India Acts to support this position. Some weaknesses of the bill such as, lack of an impartial internal review procedure, independent implementing and monitoring authorities are identified and suggestion made for solving these problems.